Facial skin aging and the use of botulinum toxin: A literature review (Research, Society and Development, 2025)
Aging, in addition to being a set of morphological, biochemical, and physiological changes, is an immutable, slow, progressive, and continuous process. As individuals age, the skin is subject to aesthetic changes that can be alleviated through the use of botulinum toxin. The aim is to analyze the use of botulinum toxin in aesthetics, focusing on facial aging, by evaluating its mechanism of action, indications, contraindications, and clinical benefits, in order to promote a comprehensive understanding of its safe and effective application in combating the signs of facial aging. This review was conducted through research on scientific articles in order to contextualize the use of botulinum toxin in both therapeutic and aesthetic fields. Botulinum toxin, popularly known as Botox, is a method used to treat wrinkles resulting from the facial skin aging process. It is a biological agent produced in the laboratory from the bacterium Clostridium botulinum, comprising seven different serotypes (A, B, C, D, E, F, and G), with type A being the most commonly used in aesthetics. To achieve satisfactory and effective results without complications, it is essential that the application of the toxin be performed correctly and by a qualified professional. Therefore, this research contributes to expanding the body of knowledge on the subject, supporting the development of further research and studies in the fields of Biomedicine and Aesthetics in general.